Begging, charity and religion in pre-famine Ireland - McCabe, Ciarán (Reappraisals in Irish history ;, 2019)
Beggars and begging were ubiquitous features of pre-Famine Irish society, yet have gone largely unexamined by historians. This volume explores for the first time the complex cultures of mendicancy, as well as how wider societal perceptions of and responses to begging were framed by social class, gender and religion.